Planificación Estratégica para la Implementación de un Cinturón Verde en la Ciudad de Riobamba, Provincia de Chimborazo - Calle Silva, Gabriel Santiago (2022)
The city of Riobamba visibly presents a lack of green spaces both in its urban and rural territory. The proposal for a green belt on the edge of the Chibunga river is oriented toward implementing a mass plan that can be detailed and consolidated in the long term, to help the city grow orderly. It is necessary to generate transversalities towards the Chibunga river area since all the facilities and services are centralized. Turning their backs on these sectors, which are the polygons of social interest, taking advantage of the natural source in the city, it will be possible to generate wide spaces that delimit uncontrolled growth and create areas for citizen activities. The research must first understand the theoretical bases necessary to understand what an urban limit is. With this, the analysis of referents helps to give a guideline of how a city expands and, in the bordering areas, what actions should be taken to realize. Then the analysis of the growth of Riobamba with the study of its facilities, mobility, urban fabric, and roads. They will help to understand why the city is expanding in a separate way to take measures to prevent this from happening. Finally, with the understanding of the theories and references added to the analysis of the current situation, it is proposed to generate some guidelines along the edge of the Chibunga river to avoid its continuous spread and create new spaces that help curb this growth and provide new areas with green places for citizens